Sanksi Adat Sebagai Hukum Alternatif Terhadap Bandar Narkoba Di Kecamatan Lhoksukon, Aceh Utara - Muhammad Yunus Ahmad (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2017)
The constitution of Indonesia Republic number 35, 2009 on narcotic has given drug traffickers from severe punishment including the death penalty. However, the drug traffickers are still existed and feeling no remorse and guilt. Given that â€œadatâ€ or the local and traditional law might be forms of alternative punishment to prevent drug crime. The research aims to examine the effectiveness of traditional law as an alternative law against drug trafficker in Lhoksukon municipal, North Aceh region, Aceh province, Indonesia. The research concludes that giving adat sanctions or local law to drug traffickers in few cases are very effective as a punishment. Due to humiliation, and they moved away from society. Yet, there are also the other cases which the traffickers got more motivated and continue to commit drug crimes. It signifies that the adat sanction is not always guaranteed for the effectiveness of punishment to drug traffickers. Nevertheless, the effect began to be felt in the community